FEASIBILITY STUDY OF TRAFFIC AND ECONOMY IN BANYUDONO - KARTASURA HIGHWAY - Intan Nuril Karimah; Nafiah Nafiah (Pondasi, 2018)
ABSTRACTPopulation and economic growth in Central Java Province continues to increase. One of the segments from the highway of Semarang-Solo is Banyudono-Kartosuro, this segment is one of the main segments that links Semarang and Solo, so stacking of vehicle volume in this region often happens. With this background, this study is entitled Feasibility Study of Traffic and Economy in Banyudono-Kartasura Highway.Analyzing the traffic aspect requires several parameters by estimating the volume of the vehicle or weather forecast, the degree of saturation and also the trip assignment value. In addition, for the economic aspects in terms of road users by calculating the value of Benefit Cost Ratio (BCR), Net Present Value (NPV), and Internal Rate of Return (IRR). Based on the forecast results obtained an outcome that in the year of 2027 for Boyolali-Kartosuro segment will experience congestion and after the built of highway, congestion will decrease in 2038, for Salatiga-Boyolali segment congestion will occurred in 2029 and after the built of highway congestion occurred in 2040. For the calculation of feasibility of economic analysis value obtained BCR = 4.3> 1, NPV = Rp 3,409,646,232,099> 0, and IRR = 12.26> 4.48%.  Keywords: Traffic feasibility, Economic growth, Banyudono-Kartosuro Highway